The revised colorectal cancer screening guideline and screening burden at community health centers - Adjoa Anyane-Yeboa; Helen Bermudez; Michelle Fredericks; Nathan Yoguez; Lynn Ibekwe-Agunanna; James Daly; Emily Hildebrant; Madhur Kuckreja; Rachel Hindin; Leslie Pelton-Cairns; Leslie Salas Karnes; Gina R. Kruse; et al. (Scientific Reports)
Abstract Colorectal cancer (CRC) is the third most common cancer among men and women combined, and the second leading cause of cancer death in the US. The revised USPSTF CRC screening recommendations increased CRC screening needs across health systems, which may create particular challenges for community health centers (CHCs) given their resource constraints. The objective of our study is to assess CRC screening rates across 10 CHCs in Massachusetts and estimate the additional increase in the number of average-risk screening-eligible individuals after the revision in guidelines. CRC screening was defined as being up to date vs. not up to date based on any of the approved screening modalities in the appropriate time frame. Our outcome of interest was CRC screening by age group and the percentage increase in screenings needed to screen individuals 45 to 49 across our partner CHCs after the revision in guidelines. Our analysis included 70,808 individuals aged 45 to 75. The overall CRC screening rate was 35.9% after the USPSTF guideline revision. Screening rates were lowest in those aged 45 to 49 at 9.6%, and highest in those over age 55 at 47.0%. There was a 22.9% increase in additional screenings needed after USPSTF guideline revision. The revised USPSTF guidelines increased screening needs by about 23% without additional funding for CHCs for which demand already outstrips staffing and clinical care resources. Future studies should include cost analyses of screening the population 45 to 49 and identify effective strategies that are low burden and do not add to the workload of CHC providers to improve screening at CHCs.